English - de Cepeda Aparicio , Leyre; Rubira-García , Rainer; Zaharia, Ana Maria (Comunicación y Género [Communication and Gender], 2023)
The National Rifle Association (NRA) has created accounts for women on different social networks to attract them into gun culture using innovative advocacy strategies aiming not only to influence their audience but also to build a positive image of the group. Here we analyze the ways of attracting the NRA female target on Instagram, considering types of women representations and roles depicted and how followers engaged during the American Midterm elections of November 8, 2022, as a key moment when public debate about gun culture increased. For this, a quantitative and qualitative study of the official Instagram account @NRAWomen has been conducted, which includes data analysis on publications, interactions, and reactions. Also, we have performed a qualitative content analysis on the most popular posts. The results show clear advertising and brand centered profitable actions as well as the systematic use of recruitment strategies based on sponsored entertainment.
Keywords: Gun culture; NRA Women; Instagram; Gender Studies; US Midterm Elections